PERAN GURU BIMBINGAN DAN KONSELING DALAM MENGATASI KEKERASAN SEKSUAL DI SEKOLAH MENENGAH ATAS - Laily Puji Astuti (Program Studi Bimbingan Konseling Pendidikan Islam Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
The main role of guidance and counseling teachers is expected to be able to overcome sexual violence in high schools. One of the functions of guidance and counseling refers to Permendikbud number 111 of 2014, guidance and counseling in repair and healing, namely helping students with problems to correct errors in thinking, feeling, willing and acting. Guidance and counseling teachers must be able to: 1) be able to prioritize the welfare of clients, 2) develop clients' cultural diversity skills, 3) develop skills in processing information and controlling emotions, 4) have high resilience in facing problems. The role of counseling and counseling teachers is an effort to prevent and overcome sexual violence in schools in good and comprehensive counseling services for all educated participants by using skills to help realize counseling and counseling services. The function of guidance and counseling can provide services to students to overcome problems by making their own decisions independently and obtaining change and better direction. Therefore, the role of guidance and counseling teachers in schools is very important in services in high schools so that they are able to understand the characteristics of students and can provide good counseling.